2019
DOI: 10.22219/jpbi.v5i2.7534
|View full text |Cite
|
Sign up to set email alerts
|

Improving student learning outcomes in science subjects through the implementation of PBL-based module

Abstract: Problem-based learning (PBL) has been reported as one of the learning models which can improve student learning outcomes optimally. Unfortunately, the frequency of implementing PBL and the teacher knowledge level about PBL is not optimal yet. This quantitative descriptive study aimed at determining the effect of PBL-based modules implementation on student learning outcomes. The population of this study was the XI grade students of SMAN 2 Wera in which the sample was the students of XI-Natural Science Class. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…The findings of this research corroborate the findings of previous work in this field advocating for the implementation of PBL in sciences education (Nursa'ban et al 2019;Thakur et al 2018;Valdez & Bungihan 2019). Furthermore, in line with Sekarini et al (2020) and Thakur et al (2018), this research suggests that the implementation of PBL provides an effective learning model that could be used in developing collaboration as a 21st-century skill.…”
Section: How Does a Beginner Physical Sciences Teacher's Problem-based Learning Implementation Enhance The Development Of Collaboration Asupporting
confidence: 87%
See 1 more Smart Citation
“…The findings of this research corroborate the findings of previous work in this field advocating for the implementation of PBL in sciences education (Nursa'ban et al 2019;Thakur et al 2018;Valdez & Bungihan 2019). Furthermore, in line with Sekarini et al (2020) and Thakur et al (2018), this research suggests that the implementation of PBL provides an effective learning model that could be used in developing collaboration as a 21st-century skill.…”
Section: How Does a Beginner Physical Sciences Teacher's Problem-based Learning Implementation Enhance The Development Of Collaboration Asupporting
confidence: 87%
“…This finding echoes the argument by Stehle and Peters-Burton (2019), who stated that collaboration enhances SDL. It further validates the finding of Nursa'ban et al (2019) that the implementation of PBL promotes SDL. The theme 'quality of the group process and outcome as a measure of success' is based on Keobiditse's response when asked to describe how he knew that collaboration had been enhanced.…”
Section: How Does a Beginner Physical Sciences Teacher's Problem-based Learning Implementation Enhance The Development Of Collaboration Asupporting
confidence: 84%
“…PBL is often assessed in its potential in various previous studies. However, various studies more often examine the effect of PBL on students' thinking skills (Anugraheni, 2018;Asyari, Muhdhar, Susilo, & Ibrahim, 2016;El-Shaer & Gaber, 2014;Ramdiah, Abidinsyah, & Mayasari, 2018), metacognition (Gholami et al, 2016;Kuvac & Koc, 2019), literacy (Febriasari & Supriatna, 2017;Shultz & Li, 2016;Suwono, Pratiwi, Susanto, & Susilo, 2017), learning outcomes (Nursa'ban, Masykuri, & Yamtinah, 2019;Yew & Goh, 2016), learning motivation (Argaw, Haile, Ayalew, & Kuma, 2017;Koçakoǧlu, Türkmen, & Solak, 2010;Thakur & Dutt, 2017), or attitudes (Demirel, 2016;Kuvac & Koc, 2018;Veli, 2014) . In fact, UEC is also a competency that needs to be optimally empowered, especially the increasingly critical environmental conditions at this time.…”
Section: Introductionmentioning
confidence: 99%
“…Effectiveness of the implementation of the PBL Module on student's achievement in Science subjects was examined by (Nursa'ban et al 2019). The study revealed that the PBL module has a significant effect on science student's learning outcomes, its utilization in teaching ensures an optimal learning ability, maximum learning outcome, and academic achievement.…”
Section: Methodsmentioning
confidence: 99%